Development of Future Compact and Eco-Friendly HVDC Gas Insulated Systems: Test Verification of Shape-Optimized DC Spacer Models - Haoluan Li; Nabila Zebouchi; Manu Haddad; Alistair Reid; Egbert Ekkel (Energies, 2022)
Spacers for the HVDC GIS/GIL play an important role in mechanically supporting conductors and separating compartments. At the same time, their insulation performance affects the stability and safety of system operation. Design rules and knowledge specific to AC spacers do not apply to those of DC spacers. Considering the shape influence on the surface electric field intensity of the spacer under HVDC applied voltage, as determined in our previous work, an optimized shape of a spacer model based on finite element electric field calculations and using standard HVAC alumina filled epoxy material and two novel types of materials were studied. The simulation’s results show that the DC shape optimization of the spacers can effectively reduce the electric field magnitudes along the spacer under different temperature gradients. To verify practically these findings, this paper presents the reduced scale gas insulated prototype that was constructed, the optimized DC spacers that were fabricated and the DC testing results using SF6-free surrounding gas: C4-Perfluoronitrile (C4-PFN, 3MTM NovecTM 4710)/CO2 and Trifluoroiodomethane (CF3I)/CO2. The results show that the shape-optimized spacer models made of conventional HVAC filled epoxy material have successfully passed the tests up to the maximum applicable ±123 kV DC exceeding thus ±119 kV DC that corresponds to the nominal voltage ±500 kV DC of the full scale.